Analisis Hubungan Produk Domestik Bruto dan Ekspor Indonesia dengan Threshold Vector Error Correction Model - Gama Putra Danu Sohibien (Jurnal Aplikasi Statistika & Komputasi Statistik, 2016)
One of the approaches that can be used to analyze the relationship between export and GDP is by using Vector Error Correction Model (VECM). In VECM, the relationship between deviation and short-term dynamics is considered to have a linear pattern. However, the pattern of it may not be linear in various economic circumtances. A A Modelwhich can be used when the relationship pattern between deviation and short-term dynamics is not linear is Threshold Vector Error Correction Model (TVECM). According to the in sample residual, TVECM with 3 regimes is better than other models (VAR, VECM, and TVECM with 2 regimes). According to out sample residual, TVECM with 2 regimes is the better than other models (VAR, VECM, and TVECM with 3 regimes).